Efficacy and acceptability of sodium picosulphate/magnesium citrate vs low‐volume polyethylene glycol plus ascorbic acid for colon cleansing: a randomized controlled trial. (18th September 2013) - Manes, G.; Amato, A.; Arena, M.; Pallotta, S.; Radaelli, F.; Masci, E.
Abstract: Aim: The study compared the efficacy, safety and tolerability of a low‐volume picosulphate/magnesium citrate preparation with that of polyethylene glycol plus ascorbic acid (PEG + ASC) in a randomized clinical trial (RCT). Method: A multicentre randomized, single‐blinded study was designed. Adult outpatients undergoing colonoscopy received either picosulphate/magnesium citrate (Group 1) or PEG + ASC (Group 2). Bowel cleansing was assessed using the Boston Bowel Preparation Scale (BBPS) and rated as adequate if ≥ 2 in each segment. Patient acceptance, satisfaction and related symptoms were recorded. Results: Two‐hundred and eighty‐five patients were included. Preparation was adequate in 75.7% of patients in Group 1 and in 76.5% of patients in Group 2. The mean BBPS scores for the entire colon and for the right colon were comparable between groups. In addition, 97.1% patients in Group 1 and 84.8% in Group 2 reported no or mild discomfort ( P  < 0.0003) and 97.8% and 83.4% expressed their willingness to repeat the preparation ( P  < 0.0001). Palatability was better in Group 1, whereas related symptoms occurred more frequently in Group 2. Regardless of which preparation was used, the split regimen was associated with better cleansing compared with the same‐day method (OR = 3.39; 95% CI: 1.1–10.4; P  = 0.03). Other predictors of poor cleansing were comorbidity, discomfort during preparation and incomplete (< 75%) preparation. Conclusion: Both picosulphate/magnesium citrate and PEG + ASC are effective for bowel preparation. Tolerability and palatability are better for picosulphate/magnesium citrate. A split schedule is associated with higher cleansing quality also for low‐volume regimens.